MiR‐26a promoted endometrial epithelium cells (EECs) proliferation and induced stromal cells (ESCs) apoptosis via the PTEN‐PI3K/AKT pathway in dairy goats. Issue 6 (15th January 2018) - Zhang, Lei; Liu, Xiaorui; Liu, Junze; Ma, Xingna; Zhou, Zhanqin; Song, Yuxuan; Cao, Binyun
Abstract : Changes in endometrial cell morphology and function are absolutely necessary for successful embryo implantation. In this study, miR‐26a was widely expressed in dairy goats, and was found to be regulated by β‐estradiol (E2) and progesterone (P4) in endometrial epithelium cells (EECs) as well as stromal cells (ESCs). Furthermore, miR‐26a played a role in the regulation of cells proliferation and apoptosis by directly regulating PTEN and indirectly regulating the PI3K/AKT pathway in EECs but not in ESCs of dairy goats in vitro. In addition, miR‐26a regulated the expression of osteopontin (OPN), vascular endothelial growth factor (VEGF), Cyclooxygenase‐2 (COX‐2), and prolactin (PRL) in endometrial cells. Therefore, we could get a conclusion that miR‐26a had very complex and diverse functions in the endometrial cells during the development of endometrial receptivity in dairy goats. This study provided an efficient platform for studying the regulatory effect of miR‐26a on endometrial cells during the development of endometrial receptivity in dairy goats. Abstract : miR‐26a promoted endometrial epithelium cells (EECs) proliferation and induced stromal cells (ESCs) apoptosis via the PTEN‐PI3K/AKT pathway in dairy goats. And miR‐26a might participate in the development of endometrial receptivity by regulating the expression of marker genes, including OPN, VEGF, COX‐2, and PRL .